[PP.27.13] USE OF 15-MINUTE AUTOMATED OFFICE BLOOD PRESSURE MEASUREMENT TO REDUCE WHITE COAT EFFECT: 24 HOUR AMBULATORY BLOOD PRESSURE MONITORING STUDY. (September 2016) - CHOI, S.; Youn, J.; Han, S.; Ryu, K.
Abstract : Objective: Repeated, automated OBPM has showed a possible alternative to 24 h ambulatory blood pressure (ABP) monitoring. We aimed to compare 15-minute blood pressure (BP) readings with the mean awake ABP. Figure. No caption available. Design and method: A total of 298 never-treated patients with high BP were enrolled. After consultation with a physician, BP was measured automatically every 3 minutes for 15 minutes, with the patient resting alone in a quiet room. Routine office BP, mean BP for 15 minutes after consultation, and BP measured at 15-minute was compared with mean awake ABP. Results: Systolic BP measured at 15 minute after consultation (144 ± 15 mmHg, p = 0.008) was approximately 2 mmHg higher than mean awake ABP. (142 ± 12 mmHg) Other BP parameters such as mean BP for 15 minutes (146 ± 15, p < 0.001) and routine office BP (152 ± 18, p < 0.001), were 4 to 10 mmHg higher than mean awake ABP. Pearson R value was highest in 15-minute SBP (r = 0.451). Especially, when systolic BP measured at 15-minute after consultation was less 160 mmHg, the difference with mean awake ABP was almost negligible. (139 vs. 140 mmHg, p = 0.207). Conclusions: In never-treated Korean hypertensives, automated office BP measured at 15-minute after consultation was well correlated with mean awake ABP. When systolic BP measured at 15 minute after consultation was less than 160 mmHg, white coat effect could virtually be prevented.